The Contribution of Inflation and Price Stability to Public Purchasing Power in Indonesia: JEL Classification: E31, E64, D12, E21 - Fesya Diva Annisa; Alfia Damar Yanti; Yehezkiel William Rossi; Maria Melisa Sutomo; Ahmad Setiawan Nuraya (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze the contribution of inflation and price stability to the purchasing power of people in Indonesia using a literature review approach. Inflation is defined as a phenomenon of general and continuous increases in the prices of goods and services that can erode people's real income. Secondary data covering the period from 2020 to 2025 shows significant fluctuations in the inflation rate and its impact on consumption capacity. The results of the data analysis indicate that the highest inflation rate occurred in 2022 at 5.51%, which coincided with the lowest point of real purchasing power. Conversely, during the 2023–2025 period, controlled inflation and the stability of the Consumer Price Index (CPI) contributed positively to an increase in real purchasing power. These findings confirm that there is a close relationship where uncontrolled inflation reduces purchasing power, while price stability plays a crucial role in maintaining the economic welfare of the community. This research recommends the importance of government policies in maintaining price stability to protect the public from economic pressure.